Scin cancer incidence rates in Krasnoyarsk Region - A. Ye. Pobilat; G. A. Arutyunyan (Бюллетень сибирской медицины)
Scin neoplasms are among the most common oncological diseases with the prevalence of basalioma. The paper рresents statistical analysis of the data of skin cancer morbidity and mortality rates in Krasnoyarsk Region summarized for the period since 1999 until 2007. In structure of the skin cancer morbidity defines a share basalioma and squamous cell carcinoma.